Formação (bildung) e teoria crítica: arquétipos para uma educação crítica na contemporaneidade - Araújo, Hermenegildo de Oliveira (2024)
This theoretical-literary thesis provides an opportunity to engage in contemporary scientific and philosophical discussions within the field of philosophy of education, focusing on the theme of formation (bildung) as a central concept. Throughout modern history, this theme has been significantly shaped by the complexities of German idealism, from its origins to the Frankfurt critical-theoretical perspective, which addresses historical-epistemological issues related to the emancipation of historical subjects engaged in transformative praxis of social reality (the current period reduces education to mere "knowhow" and commodity). The effects observed allow individuals to become human, assuming formative purposes that, in their conceptual complexity, significantly contribute to the development of reflections on humanity, education, and their humanity, as well as the social and political organizations to which they belong. The key question forming the problem/object of this thesis is: How can we theoretically and concretely conceive critical formation (bildung) with a view to the emancipation of historically recognized and self-determined subjects within a context marked by frank antinomies that hinder freedom and autonomy due to contingent postmodern narratives? It is considered, however, that formation (bildung) is a spiritual and intellectual process that never ceases, and in our thesis, despite its polysemy, we detect that for it to be effective, it needs to delve into various fields of human knowledge in its historicalepistemological concreteness, such as history, sociology, philosophy, psychology, anthropology, economics, geography, literature, political science, logic, among others. That said, the findings of this research, which have emerged with formation (bildung) as the central focus, have shaped the methodological organization of the thesis into four chapters. The first chapter presents an argument aiming to trace, through a state-of-the-art review, the classical concept of formation (bildung), including its etymology and its material bases, with the historically self-determined subject receiving critical emancipatory formation. In the second chapter, we analyze in light of critical theory that focuses on modernity and postmodernity as cultural forms of specific historical periods related to intellectual formation. The third chapter discusses the crisis of reason and alienation as an epochal development stemming from this crisis, confirming the distortion in the formation process of historical subjects. In the final chapter, we argue about the impasses and possibilities, using critical theory as a substantive theoretical framework for mass education based on a critical formation (bildung) that dialectically supports the subject's freedom, prospecting their emancipation in the present and concrete history. Indeed, grounded in Marxist critical theory, we notably critique reified education and its equally reified formation (bildung) process, which entails alienation and spiritual and intellectual deformation of the historical subject, whose subjectivity is eroded due to deformative structures expressed by the sociometabolic logic of capital. In this sense, the reflections articulated here exhibit an unequivocal concern with the Brazilian educational reality, emphasizing the necessity to recognize the historicalconcrete materiality underpinning the contradictions and experiences within the formation process of historical subjects. Thus, the historical-concrete materiality presumed within the totality cannot be overlooked in supposedly critical analyses when education serves as an avenue for scientificphilosophical investigation.